Embodied Islam and Coastal Existence: Maritime Cultural Da’wah on Environmental Sustainability in Patorani Communities - Nasriah, St. Nasriah; Ramli, Ramli (LPPM IAIN Parepare, 2025)
Coastal Muslim populations are increasingly facing ecological degradation, climate uncertainty, and the deterioration of traditional fishing practices, prompting essential enquiries into the manifestation and mobilisation of religious values in evolving maritime contexts. This study examined the Patorani fishing tradition in South Sulawesi via the framework of Maritime Cultural Da’wah, defined as an embodied Islamic discursive tradition. The research employs a qualitative-interpretive design, incorporating discourse and narrative analysis derived from data gathered from twelve intentionally selected participants, including fishermen, ritual specialists, and community leaders, supplemented by extensive participant observation and ethnographic documentation. The data were transcribed and analysed using a mixed inductive-deductive coding framework that emphasised moral vocabularies, ceremonial lexicons, authority structures, and ecological practices inherent in maritime life. The findings indicate that Islamic values are conveyed not chiefly through formal doctrinal teaching but are manifested through three interconnected domains: ritualised risk governance based on tawakkul, collective decision-making organised through layered shura, and a moral economy of distribution that prioritises fairness and social solidarity. The study conceptually extends Maritime Cultural Da’wah as a theoretical framework that elucidates the reproduction of Islamic ethical fishing. This study enhances worldwide discussions on religion and sustainability by demonstrating that indigenous fishing practices can act as repositories of ecological wisdom, ethical management, and communal resilience. It provides practical implications for coastal policy, indicating that the preservation of maritime cultural practices is essential for both protecting cultural heritage and promoting sustainable, community-based fisheries management amid environmental change.